MULTINATIONAL CORPORATIONS IN THE CREATIVE INDUSTRIES AND SPECIFICS IN ITS MANAGEMENT - Kharabuha, Yevhen; Pichanič, Mikuláš, 1942-; Mayerhoffer, Manuel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The topic of the paper is connected to management of the business units involved in multinational level of operations. Nowadays, we are witnessing a growing importance of the creative economy. It is expressed in its evolving contribution share to the world GDP as well as the increasing importance of creative economy as employer across different countries and wide range of its industries. It is accompanied by future significance of the creative economy in terms of employment, as due to the technological development certain jobs can simply be eliminated. The creative economy has distinctive difference from the traditional economy. Thus, it has its own features for management of organizations involved in this type of economy. One of the growing sectors in this economy is becoming the design and new media, which includes the video game design. Low investigation level of the video gaming business management has become one of the main reasons for this paper development. Thus, the main goal of this Master Thesis could be defined as investigation of management features of multinational companies engaged in the video game industry, using the real example of Activision Blizzard company.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses